Pandangan pelajar dan guru terhadap tahap kesukaran tajuk-tajuk kimia - Ibrahim, Dani Asmadi; Othman, Azraai; Talib, Othman (Faculty of Education, University of Malaya, 2015)
This research paper discusses a survey to compare the students and chemistry teachers point of views on the level of difficulty in semester one chemistry topics in one-year matriculation program. The study involved 30 teachers and 159 students in a single matriculation college. The group of students consists of different levels in chemistry achievement and also different in three academic sessions. Difficulties of Chemistry Topics Questionnaires are used to assess the view on the difficulty level of chemistry topics. Data from the Difficulties of Chemistry Topics Questionnaire are ordinal type and been analyzed using Friedman test to compare the difficulty level of chemistry topics in semester one. Comparison on difficulty level of the topic indicates that, there is a difference between the views of teachers and students regarding which the most difficult topic. Chemistry teacher believes that the most two difficult topic is the ionic equilbria (chapter 7) and atomic structure (chapter 2), and for students, the most two difficult topic are the ionic equilbria (chapter 7) and chemical equilbrium (chapter 6). Based on the student comments in the survey, it was found that the most frequent difficulties mentioned are misunderstanding in study of chemistry concepts. Besides that, it also found that, sequence of difficulty level of the topic is same as the sequence of topics to be studied during the first semester. Students believed that the first topic to be learned is the most simple and the last topic is the most difficult to learn. For conclusion, some recommendations have been proposed to improve the teaching and learning of the chemistry in semester one.